A simple technique of intraocular lenses explantation for single-piece foldable lenses - Arup Bhaumik; Santanu Mitra (Indian Journal of Ophthalmology, 2017)
Foldable intraocular lenses (IOLs) are most commonly used in modern-day cataract surgery. Explantation of these IOLs is not frequently encountered, but sometimes extreme situations may demand the same. Commonly explantation is achieved by bisecting the IOL inside the anterior chamber with a cutter and delivering the pieces out one by one. This may require corneal wound extension with associated damage and endothelial loss leading to visual deterioration. We devised a simple, innovative IOL explantation technique utilizing a modified Alcon A cartridge and snare. This can successfully refold the IOL to be explanted inside the eye and deliver it out through the same wound. The device has limitations with very thick optic lenses, multipiece, and silicon IOLs. In conclusion, we describe a simple, innovative, and reproducible technique to explant almost any single piece IOL without compromising the original surgery and yielding very satisfactory outcomes.